ANALYSIS DEVELOPMENT OF E-GOVERNMENT ON PROVISION OF INFORMATION ACCESS IN CENTRAL JAVA’S PROVINCE LIBRARY - Alif, Muhammad; Warsono, Hardi (Journal of Public Policy and Management Review, 2019)
Globalization is a phenomenon where people expect a much more effective and efficient interaction than before, both directly and indirectly. The Provincial Government of Central Java utilizes technological advances in the current era of globalization to fulfill the needs of citizens. Central Java Province Library under the Departement of Archives and Central Java Library innovates by implementing the concept of e-government. Central Java Provincial Library oriented to public services. Where they provide an easy access for people who want to do library activities through e-government. The e-government programs owned by the Central Java Provincial Library include websites, iJateng, RFID, InlisLite, RBM, and other electronic facilities. The research method used is descriptive qualitative. Primary data is collected through interviews with government officials who are authorized and directly involved in e-government activities and field observations. Meanwhile, secondary data is collected through information available on the Central Java Province Library website and data obtained from the site. The results showed that the implementation of e-government was good, but in the development of e-government there were still some problems in Human Resources and existing facilities. It is recommended that the results of this study can be a boost in the development of e-government in the Central Java Provincial Library which is better than before, so that it can provide more optimal public services to the visitors.